2007
DOI: 10.1093/nar/gkm501
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome dynamics-based operon prediction and verification in Streptomyces coelicolor

Abstract: Streptomyces spp. produce a variety of valuable secondary metabolites, which are regulated in a spatio-temporal manner by a complex network of inter-connected gene products. Using a compilation of genome-scale temporal transcriptome data for the model organism, Streptomyces coelicolor, under different environmental and genetic perturbations, we have developed a supervised machine-learning method for operon prediction in this microorganism. We demonstrate that, using features dependent on transcriptome dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 59 publications
2
34
0
4
Order By: Relevance
“…The cotranscription of the cps genes in D39 was determined by intergenic RT-PCR essentially as described previously (51). The cDNA molecules (cDNAs) of D39 were prepared using total RNA preparation (described above) with an iScript cDNA synthesis kit (Bio-Rad, Beijing, China) as instructed by the supplier.…”
Section: Methodsmentioning
confidence: 99%
“…The cotranscription of the cps genes in D39 was determined by intergenic RT-PCR essentially as described previously (51). The cDNA molecules (cDNAs) of D39 were prepared using total RNA preparation (described above) with an iScript cDNA synthesis kit (Bio-Rad, Beijing, China) as instructed by the supplier.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 1 µg of RNA was converted to cDNA, and primers amplifying a region of the xdhB gene were chosen for semiquantitative PCR. The rpoA gene ( SCO4729 ), encoding the α‐subunit of RNA polymerase, was also used as a control; rpoA is transcribed as part of an operon containing ribosomal protein genes (Charaniya et al ., ) and its expression is expected to decrease on exposure to serine hydroxamate. Relative to hrdB , expression of xdhB was increased ∼2‐fold, whereas rpoA expression was reduced after 30 min incubation with serine hydroxamate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The differential expression of genes within the abeABCD operon is not unprecedented in S. coelicolor (9), but it also is not considered to be the norm. Microarray studies of S. coelicolor gene expression have shown that the first gene of an operon is typically the most highly expressed, with expression levels then decreasing throughout the length of the operon (26).…”
Section: Discussionmentioning
confidence: 99%